2x+y=10x+90

Simple and best practice solution for 2x+y=10x+90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+y=10x+90 equation:


Simplifying
2x + y = 10x + 90

Reorder the terms:
2x + y = 90 + 10x

Solving
2x + y = 90 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
2x + -10x + y = 90 + 10x + -10x

Combine like terms: 2x + -10x = -8x
-8x + y = 90 + 10x + -10x

Combine like terms: 10x + -10x = 0
-8x + y = 90 + 0
-8x + y = 90

Add '-1y' to each side of the equation.
-8x + y + -1y = 90 + -1y

Combine like terms: y + -1y = 0
-8x + 0 = 90 + -1y
-8x = 90 + -1y

Divide each side by '-8'.
x = -11.25 + 0.125y

Simplifying
x = -11.25 + 0.125y

See similar equations:

| x(3x+54)(2x)=360 | | -8+6x=2x+16 | | X=4x-3x-10 | | -30+-80= | | 11x-(2x-5)=32 | | 10x+4=12x-15 | | -.72x=-1.44 | | X-6x=-35 | | 6(5-8w)+12=54 | | 71+(-71)= | | 4(-3-y)-3(-3)=-7 | | 4(1x-6)+4=6x-6 | | 4x+6x-60=45-5x | | 90=x+13+x | | -11x-9=-64 | | 2(b+2)=-4(b+7)-2b | | 48=32-2(x-3) | | -5(1+6b)=-8b+36 | | P^3+57=q^2 | | Q=12 | | 4x=6x-34 | | 25+(-20)= | | 20+3y=y+21-2y | | -[8z-(19z+10)]=10+(10z+5) | | x^2-6x+y^2+2y-15=0 | | 1=-0.5B+B | | 17-18k=-15 | | 8m-6=m+8 | | 8n-(3+8)=22 | | 0.50x+0.45(50)=32.5 | | 9x^2+18xy+8y^2= | | 4x+17-3x=7+4x-5 |

Equations solver categories